BORRELIA RECURRENTIS AS A CAUSE OF HIGH GRADE FEVER IN RAWALAKOT, AZAD KASHMIR - Malik, Nasrullah; Butt, Tariq; Bari, Irfan ul; Haider, Irfan Zafar (Pakistan Armed Forces Medical Journal, 2006)
Background: A descriptive study was conducted at Combined Military Hospital Rawalakot, Azad Kashmir to determine the frequency of Borrelia recurrentis. Patients and Methods: Both out door and indoor cases were included. A total of 80 febrile patients with temperature above 1000C were studied. Cases showing any other cause of fever on routine / available tests were excluded. Borrelia recurrentis was sought by Giemsa stain. All positive cases were treated with Doxycycline. Results: Nine cases were positive (11.25%). Treatment response was 100%. Conclusion: Borrelia recurrentis is found in a significant number of febrile cases at Rawalakot Azad Kashmir.